PENGARUH INTERVENSI MEDIA SOSIAL (WHATSAPP) DENGAN FLYER TERHADAP PERUBAHAN PERILAKU MEROKOK REMAJA PADA MASA PANDEMI COVID-19 DI DESA TOMADO KECAMATAN LINDU - Yusuf, Yusuf; Agus, Nur Indriani; Syafar, Muhammad (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Adolescent smoking behavior is a behavior that endangers health, but there are still many teenagers who become smokers who started when they were teenagers or at the age of 11 years, especially teenage boys who often did this action. The use of appropriate media can affect the knowledge of respondents. In general, this study aims to determine the effect of social media intervention (whatsapp) with flyers on changes in adolescent smoking behavior during the COVID-19 pandemic in Tomado Village, Lindu District, Sigi Regency, Central Sulawesi. And specifically, the research objective was to determine the effect of social media intervention (whatsapp) with flyers on smoking knowledge, smoking frequency, changes in smoking attitudes, and adolescent motivation to quit smoking. This type of research is a quasi-experimental design with a pretest-posttest two group design. The research sample used purposive sampling method and obtained a sample of 40 people. The instrument of this research used questionnaires, observation sheets, pretest and posttest questionnaires, and media flyers. Analysis of research data using a comparative test, namely Paired sample t-test, and Independent t-test. The results showed that there was a significant difference in respondents' knowledge about the dangers of smoking in the intervention group, while in the control group it was found that there was no significant difference in respondents' knowledge; there was a significant difference in the frequency of adolescent smoking in the intervention group and the control group; there is a significant difference in adolescent smoking attitudes in the intervention group and the control group; there was a significant difference in motivation to quit smoking in the intervention group and the control group.